Enhanced photocatalytic degradation of organic pollutants by Ag–TiO2 loaded cassava stem activated carbon under sunlight irradiation. (September 2022) - Sathishkumar, K.; Sowmiya, K.; Arul Pragasan, L.; Rajagopal, Rajakrishnan; Sathya, Rengasamy; Ragupathy, S.; Krishnakumar, M.; Minnam Reddy, Vasudeva Reddy
Abstract: Ag-doped TiO2 and Ag-doped TiO2 loaded cassava stem activated carbon (Ag: TiO2 /CSAC) were prepared by sol-gel method and are labelled as AT and AT/CSAC respectively. XRD results confirmed that the anatase-TiO2 and crystalline size are decreased (12.37 nm) through the silver doping and cassava stem activated carbon loading. UV–Vis showed that the AT/CSAC makes a red shift from the absorption edge compared to pure and AT samples and then the band gap is reduced (2.81 eV). The increased surface area (238.51 m 2 /g) of the AT/CSAC sample through the Ag and CSAC, respectively. The consequences point out that the highest photodegradation efficiency (98.08%) of the TiO2 upon silver doping and cassava stem activated carbon loading samples were brilliant green (BG) under sunlight irradiation. Highlights: Ag-doped TiO2 loaded cassava stem activated carbon (Ag: TiO2 /CSAC) were prepared by sol-gel method. Ag: TiO2 /CSAC showed that the particle size, band gap are also reduced and its was increased surface area. The photocatalytic results indicate that Ag: TiO2 /CSAC effectively degrade BG under sunlight.